Efficacy of simultaneous placement of dental implants in osteotome-mediated sinus floor elevation with and without bone augmentation: A systematic review and meta-analysis - Priyanka Sunil Rahate; Rajashri Abhay Kolte; Abhay Pandurang Kolte; Girish Haripal Bodhare; Vrushali Nilesh Lathiya (Wolters Kluwer Medknow Publications, 2023)
Background: The aim of the present systematic review was to assess the effectiveness of simultaneous placement of implant in osteotome-mediated sinus floor elevation (OMSFE) procedure with and without bone augmentation. Materials and Methods: An exploration of randomized clinical trials (RCTs) was systematically done in three databases comprising PubMed, Cochrane, and Google Scholar complemented by a thorough manual search of periodontology/implantology-related journals. A final inclusion of 6 RCTs (2010-2020) was done to investigate the efficiency of simultaneous implant placement with OMSFE in conjunction with bone augmentation. A meta-analysis was further conducted with comparable studies which assisted in attaining a final conclusion regarding the survival rate, endosinus bone gain (ESBG), and marginal bone loss (MBL). Results: Data synthesis was performed on the basis of 6 trials and further meta-analysis was performed to statistically validate the clinical and radiographic outcomes. Meta-analysis on the parameters indicated greater ESBG (mean difference [MD]: 0.82; [95% confidence interval [CI]: 0.72-0.91, P ≤ 0.0001]), which was also associated with minimal MBL (MD: −1.11; [95% CI: −1.53-0.68, P ≤ 0.0001)] in the bone augmentation group. However, the parameter of implant survival rate (risk ratio: 1.04; [95% CI: 0.83-1.31, P = 0.6849)] failed to reveal significant difference between the two groups. Conclusions: In the restoration of masticatory apparatus, simultaneous placement of implant in OMSFE with bone augmentation can be considered as successful and predictable treatment approach in deficient posterior maxillary ridges. It contributes toward bone neoformation resulting in greater ESBG as well as a substantial decrease in MBL.